Construction planning - Neale, R. H.; Neale, David E.; Stephenson, Paul (ICE Publishing, 2016)
Construction Planning is a thorough guide to the use of planning techniques, key concepts and the latest developments in the field of project planning. It explores the construction planning process in the digital age by taking a closer look at the most effective principles and practice, including the latest technological developments to support the successful delivery of projects.